2014
DOI: 10.1007/s00253-014-6308-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of l-lysine α-oxidase from Scomber japonicus in Escherichia coli for one-pot synthesis of l-pipecolic acid from dl-lysine

Abstract: L-Pipecolic acid is a key component of biologically active molecules and a pharmaceutically important chiral building block. It can be stereoselectively produced from L-lysine by a two-step bioconversion involving L-lysine α-oxidase and ∆(1)-piperideine-2-carboxylae (Pip2C) reductase. In this study, we focused on an L-lysine α-oxidase from Scomber japonicus that was originally identified as an apoptosis-inducing protein (AIP) and applied the enzyme to one-pot fermentation of L-pipecolic acid in Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…Additional overexpression of the E. coli gene for lysine uptake, lysP, accelerated L-PA formation from L-lysine about five fold (Fujii et al 2002). Biotransformation of racemic DL-lysine with E. coli overproducing L-lysine α-oxidase from S. japonicus yielded high titers (about 45 g L −1 ) of optically pure L-PA (Tani et al 2015). The functionality of L-lysine cyclodeaminase from Actinoplanes friuliensis has been shown in C. glutamicum (Wagner et al 2010), and the enzyme from Streptomyces.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additional overexpression of the E. coli gene for lysine uptake, lysP, accelerated L-PA formation from L-lysine about five fold (Fujii et al 2002). Biotransformation of racemic DL-lysine with E. coli overproducing L-lysine α-oxidase from S. japonicus yielded high titers (about 45 g L −1 ) of optically pure L-PA (Tani et al 2015). The functionality of L-lysine cyclodeaminase from Actinoplanes friuliensis has been shown in C. glutamicum (Wagner et al 2010), and the enzyme from Streptomyces.…”
Section: Discussionmentioning
confidence: 94%
“…L-PA accumulated intracellularly when Escherichia coli overproducing L -lysine 6-dehydrogenase from S. pomeroyi was grown in L-lysine-containing media (Neshich et al 2013). L-PA was produced from L-lysine in biotransformations with E. coli overproducing either L-lysine α-oxidase from Scomber japonicus (Tani et al 2015) or LAT (Fujii et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…l -PA, an important chiral precursor for the synthesis of optically pure piperidine rings, forms core structure of many naturally occurring alkaloids and drugs in clinical use [9, 18]. l -PA can be biosynthesized using crude enzymes or whole-cell biocatalysts [14, 15, 19], and several of the different catalytic steps involved have been investigated, including some that are unstable and accompanied by high manufacturing costs that limit their applications. However, few researchers have focused on the direct fermentation of l -PA, even though fermentation potentially offers an alternative, efficient, low cost method [22].…”
Section: Discussionmentioning
confidence: 99%
“…The second involves the loss of the ε-nitrogen and incorporation of an α-nitrogen into l -PA (P6C pathway). Several studies on the enzymatic production of l -PA using enzymes from both pathways have been reported [14, 15]. For example, Neshich et al, obtained l -pipeclic acid on lysine containing medium (about 0.6 μg/mg protein) using recombinant E. coli cells over-expressing the l -lysine 6-dehydrogenase gene in P6C pathway [16]; Fujii et al reported that about 3.9 g/L of optically pure l -PA was biosynthesised using the enzymes from the P2C pathway [17].…”
Section: Introductionmentioning
confidence: 99%
“…The UV absorbance at 280 nm was mensurated as the protein concentration by SpectraMax M2 e (Molecular Devices, American) (Annamalai et al, 2011; Zhang et al, 2008). Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) was used to analyze the purity of purified enzymes with a 12 % acrylamide gel (Tani et al, 2015a)2…”
Section: Methodsmentioning
confidence: 99%